2000
DOI: 10.1038/35011084
|View full text |Cite
|
Sign up to set email alerts
|

A receptor for phosphatidylserine-specific clearance of apoptotic cells

Abstract: cytosis of cellular corpses. During apoptosis, the asymmetry of plasma membrane phospholipids is lost, which exposes phosphatidylserine externally. The phagocytosis of apoptotic cells can be inhibited stereospecifically by phosphatidylserine and its structural analogues, but not by other anionic phospholipids, suggesting that phosphatidylserine is specifically recognized. Using phage display, we have cloned a gene that appears to recognize phosphatidylserine on apoptotic cells. Here we show that this gene, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
1,058
1
19

Year Published

2000
2000
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,364 publications
(1,116 citation statements)
references
References 30 publications
26
1,058
1
19
Order By: Relevance
“…Eryptotic cells bind to phosphatidylserine receptors on macrophages [22], which engulf and degrade phosphatidylserine-exposing cells [8]. Accordingly, eryptotic cells are rapidly cleared from circulating blood [36], and stimulation of eryptosis leads to anemia, if the accelerated loss of circulating erythrocytes is not matched by a similarly increased formation of new erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Eryptotic cells bind to phosphatidylserine receptors on macrophages [22], which engulf and degrade phosphatidylserine-exposing cells [8]. Accordingly, eryptotic cells are rapidly cleared from circulating blood [36], and stimulation of eryptosis leads to anemia, if the accelerated loss of circulating erythrocytes is not matched by a similarly increased formation of new erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular mechanisms participating in the clearance of apoptotic cells by macrophages have been described in detail and, to a lesser extent, this can be said about non-professional phagocytes. 14,18,19,26,27 It has been suggested that autophagy as a mechanism of cell death may have been developed because in some forms of PCD the availability of engulfing cells is insufficient for the clearance of dead cells and autophagy has been evoked for elimination of excess cells by their own lysosomes. 13 In the present study we clearly demonstrate this is not the case: autophagic MCF-7 cells of different origin are recognized and eaten by both differentiated macrophages and non-dying MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…1). The protein was initially identified as the receptor of phosphatidylserine, a specific marker present at the surface of apoptotic cells, and is involved in apoptotic cell phagocytosis (Fadok et al, 2000). However, PTDSR is localized in the nucleus (Cikala et al, 2004;Cui et al, 2004).…”
Section: Ptdsrmentioning
confidence: 99%